1998
DOI: 10.1152/ajpregu.1998.275.6.r1958
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of milk-borne insulin in the development of pancreatic amylase at the onset of weaning in rats

Abstract: The development of pancreatic amylase activity was examined in rats fed in regular cages or in special cages, designed so the pups could not reach solid food to prevent weaning. In both groups, the amylase activity in zymogen granules increased in rat pups aged 14 days, peaked at 18 days, and thereafter remained at a 1.6-fold higher level than at 14 days of age. An increase in the plasma concentration of immunoreactive insulin preceded the increase of amylase activity, whereas the plasma concentration of C-pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 25 publications
2
29
2
Order By: Relevance
“…The oral insulin effect on intestinal digestion and absorption was disappeared after weaning (28-30-day-old-rats). It should be noted that the oral hormone effect on the intestinal carbohydrate hydrolysis and absorption is most pronounced when insulin level elevates in the suckling serum and breast milk [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The oral insulin effect on intestinal digestion and absorption was disappeared after weaning (28-30-day-old-rats). It should be noted that the oral hormone effect on the intestinal carbohydrate hydrolysis and absorption is most pronounced when insulin level elevates in the suckling serum and breast milk [16].…”
Section: Discussionmentioning
confidence: 99%
“…The level of corticosterone [14], thyroxin [15] and insulin [16] increases in the rat serum together with abrupt shifts in the structure and function of the small intestine at the time of weaning [1][2][3][4][5][6][7][8]. Moreover, insulin level is elevating as in the suckling blood and in their mother breast milk [16]. Oral administration of insulin causes an increase of the pancreatic α-amylase activity which takes part in the initial stage of carbohydrate hydrolysis in small intestine in suckling rats [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean molecular weight (ϳ900) and the molecular weight distributions of the hydrolysate (Table 1) were obtained by means of HPLC with a TSKgel G2000SWxl column (TOSOH, Tokyo, Japan). We collected rat milk from 7 to 13 days after birth and measured the protein concentration, following a previously described method (20), and the results showed that protein concentration of rat milk during the period was 7.9 Ϯ 0.7%. Thus, in the present study, protein content of the milk formulas was set at 7.5% (Table 2), and the compositions of fat and carbohydrate and energy of both milk formulas were also set likewise (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…On day 7, 80 pups, male and female, were randomly divided into two artificial rearing groups (Prot and Hydr, n ϭ 30 and 30) and a dam-fed (DF) group (n ϭ 20) of equal mean body weight. Rat pups for artificial rearing were implanted with an intragastric catheter made of polyethylene tubing at 7 days of age, and the pups were fed either of the milk formulas following a procedure described previously (20). Briefly, the intragastric cannula was joined to a polyethylene lead tubing, which was connected to a formula-filled syringe mounted on an infusion pump (model pump 44; Harvard Apparatus, South Natick, MA).…”
Section: Methodsmentioning
confidence: 99%